Investigation of control system operation in plug-in four-wheel drive of wheeled vehicles on roller test benches - A. I. Fedotov; O. S. Yankov; D. O. Ukhvatov (Вестник СибАДИ)
Introduction. Modern wheeled vehicles are equipped with plug-in all-wheel drive control systems that increase their trafficability, stability and controllability. A good example is the AWD (All-wheel drive) system, which provides the highest efficiency of a plug-in drive compared to a permanent all-wheel drive. In order to ensure and maintain the efficiency and safety of vehicles with plug-in all-wheel drive control systems, it is necessary to investigate their functioning during manufacture and operation stages. Road testing methods are the most widespread methods for testing the systems under consideration. However they are not always feasible in the conditions of enterprises which provide testing and examination of vehicles, as well as in the conditions of service stations, service centers and other organizations of the automotive industry.   Materials and methods. For the purpose of analytical research, a developed set of mathematical models containing the “ Vehicles “ and the “Stand” subsystems models was used. The description of the models is completed with the software package “Universal mechanism-9”. Experimental studies of operation of the vehicle with an automated AWD system were carried out on a full-support multifunctional stand with IRNIT running drums. The Volvo S60 25T AWD automobile with Haldex clutch of II generation was used as a research object.   Results and discussion. In the course of analytical and experimental studies, the results of investigating vehicle operation were obtained by simulating acceleration with the slipping of the driving wheels of both the front and rear axles: the traction force on the driving wheels and the wheel speed.   Conclusion. The results of this analytical research and their correspondence to the results of experimental study show the possibility of conducting qualitative and quantitative testing of automobiles with plug-in all-wheel drive control systems on roller test benches. The use of a complex of mathematical models will further allow for the development of unique bench methods and equipment to carry out research on the operational properties of modern vehicles.